Community Engagement: An Integral Component of a Multifaceted Conservation Approach for the Transboundary Western Pacific Leatherback - Pakiding, Fitryanti; Zohar, Kartika; Allo, Alberto Y. T.; Keroman, Sinus; Lontoh, Deasy; Dutton, Peter H.; Tiwari, Manjula (Frontiers in Marine Science, 2020)
The Biodiversity Impact Mitigation Hierarchy (BIMH) has been proposed as an improved, holistic, and integrative approach for fisheries management and biodiversity conservation. The first three BIMH steps – avoid, minimize, and remediate – take place at sea where fishing activity is taking place. However, these on-site measures are costly and difficult to effectively implement across the vast range of a highly migratory species. Therefore, remaining residual negative impacts need to be addressed by compensatory off-site conservation measures, e.g., at sea turtle nesting beaches. As a case study of a conservatory offset to fisheries bycatch, we use the critically endangered leatherback sea turtle nesting population on Jamursba-Medi and Wermon Beaches in Papua Barat, Indonesia. We describe the implementation of multi-level conservatory offsets for this population through nesting beach protection, optimization of reproductive output, and innovative approaches to engage local communities in leatherback conservation. While improved nest protection measures have helped optimize hatchling production, the engagement of the local communities, through activities that empower and enhance quality of life, has been an integral and critical component to the successful increase in hatchling productivity on these beaches. This momentum needs to be sustained and scaled-up to protect the majority of threatened nests over a consistent number of years to successfully provide the recruitment boost needed at the population level. These compensatory off-site conservation measures are also the most cost-effective means of achieving increases in leatherback populations, and perhaps the most critical component of the recovery strategy for Pacific leatherbacks.